2016
DOI: 10.3390/su8030283
|View full text |Cite
|
Sign up to set email alerts
|

Why, How and What do Organizations Achieve with the Implementation of Environmental Management Systems?—Lessons from a Comprehensive Review on the Eco-Management and Audit Scheme

Abstract: Abstract:The Eco-Management and Audit Scheme (EMAS) was established in 1993 in the European Union as a voluntary instrument facilitating the implementation of organisational environmental policies and management of environmental aspects. We present a comprehensive literature review on EMAS research, organized according to three broad questions: Why do organisations choose EMAS? How is the scheme implemented and adapted to organisational characteristics? And what results are achieved? We have built analysis mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 77 publications
2
19
0
Order By: Relevance
“…Tourais and Videira also analyzed [9], through a literature review of 80 papers, the motives and benefits that drive organizations to adopt the EMAS.…”
Section: Description Of the Iso 50001 Standard And Literature Reviewmentioning
confidence: 99%
“…Tourais and Videira also analyzed [9], through a literature review of 80 papers, the motives and benefits that drive organizations to adopt the EMAS.…”
Section: Description Of the Iso 50001 Standard And Literature Reviewmentioning
confidence: 99%
“…The first three interviewed experts from associations provided the following ideas: they suggested putting resource efficiency and financial performance together and analyze in how far the one causes the other (#16); analyzing material, water, or energy consumption in a certain process to financial performance at this point (#17); and analyzing financially strong corporations, look at how they deal with resource efficiency, e.g., Eco-Management and Audit Scheme (EMAS) [67], and check if these corporations have a systematic management regarding resource efficiency (#18).…”
Section: The Non-practitioners' Views On the Relationship And Its Meamentioning
confidence: 99%
“…In order to perform the initial search of relevant articles, the Scopus database (Elsevier, Amsterdam, The Netherlands) of peer-reviewed literature was selected. Scopus, which possesses an extensive global coverage of research articles, enabling researchers to capture a wide range of relevant publications, has been widely used for systematic review studies [39][40][41]. Thus, we confined the review to the extant literature found in journal articles referenced by this database.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we confined the review to the extant literature found in journal articles referenced by this database. wide range of relevant publications, has been widely used for systematic review studies [39][40][41]. Thus, we confined the review to the extant literature found in journal articles referenced by this database.…”
Section: Methodsmentioning
confidence: 99%